2011
DOI: 10.3109/01902148.2011.605512
|View full text |Cite
|
Sign up to set email alerts
|

Interferon-γ and tumor necrosis factor-α act synergistically to up-regulate tissue factor in alveolar epithelial cells

Abstract: Fibrin deposition mediated through activation of tissue factor (TF) in the airspace is central to the pathogenesis of acute lung injury. Defining the mechanisms of TF regulation in the lung is critical to understanding pulmonary fibrin formation. Tumor necrosis factor-α (TNF-α) upregulates TF in the injured lung, and there is emerging evidence that another cytokine, interferon-γ (IFN-γ) also modulates expression. The effects of TNF and IFN on regulation of TF were studied in alveolar epithelial A549 cells. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 36 publications
0
16
0
Order By: Relevance
“…Previous studies have demonstrated that TNF‐α increased TF expression and cell surface TF activity of alveolar epithelial A549 cells (32). Moreover, increasing concentrations of TNF‐α resulted in a graded increase of TF expression in cultured VSMCs (33).…”
Section: Discussionmentioning
confidence: 95%
“…Previous studies have demonstrated that TNF‐α increased TF expression and cell surface TF activity of alveolar epithelial A549 cells (32). Moreover, increasing concentrations of TNF‐α resulted in a graded increase of TF expression in cultured VSMCs (33).…”
Section: Discussionmentioning
confidence: 95%
“…In this study, we evaluated the cytotoxicity induced by a mixture of proinflammatory cytokines (IL-1β/ TNF-α/IFN-γ), which have been suggested to play major roles in sepsis or ALI (5,(8)(9)(10)(11)(12)(13), in the human alveolar epithelial cell line A549. Then, to clarify the cytotoxic signaling pathways responsible for alveolar epithelial cell injury, various agents with antiinflammatory or antioxidative properties were screened for cytoprotective effects in an in vitro acute lung injury model (9,(14)(15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%
“…Then, to clarify the cytotoxic signaling pathways responsible for alveolar epithelial cell injury, various agents with antiinflammatory or antioxidative properties were screened for cytoprotective effects in an in vitro acute lung injury model (9,(14)(15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%
“…Patients who died had a trend toward a higher MP concentration in lung edema fluid compared with those who survived (P ϭ 0.073), attesting to a detrimental effect of MPs in ALI/ARDS. Similar MPs could be generated in vitro by stimulation of cultured alveolar epithelial cells with a mix of the proinflammatory mediators TNF-␣, IL-1␤, and interferon-␥ (16,17). Whereas both ARDS and non-ARDS controls in Bastarache's study were severely sick, BALF analyses from healthy pigs with volume-controlled ventilation set to maintain normocapnia (37.5-41 mmHg Pa CO 2 ) with 5 cmH 2 O positive endexpiratory pressure revealed PMPs that were positive for fibrinogen, vWF, and P-selectin (124).…”
Section: Potential Detrimental Effects Of Microparticles In Alimentioning
confidence: 94%